Augmenting pomelo juice quality through membrane-based clarification and bioactive compounds recovery - Mohd Nor, Mohd Zuhair; Mokhtar, Mohd Noriznan; Katibi, Kamil Kayode; Md. Yunos, Khairul Faezah; Shamsudin, Rosnah; Shitu, Ibrahim Garba (Taylor and Francis Ltd., 2024)
The presence of impurities, microorganisms, enzymes, suspended solids, and impurities in unclarified pomelo juice negatively affected the quality and shelf-life of the product in the food industry. The objective of this study focuses on the clarification of fresh pomelo juice using an ultrafiltration (UF) process. The study examined the influence of the operating pressure (OP) on the various quality attributes of pomelo juice, such as pH, total soluble solids (TSS), turbidity, color, total phenolic content (TPC), ascorbic acid content (AAC) and fouling mechanisms and permeate flux (J) behavior. To perform the clarification of pomelo juice, a 100 kDa membrane (polymeric) was used in a dead-end system, and the process was carried out in batch mode at OP values of 1.0, 1.5, 2.0, 2.5 and 3.0 bar. The findings revealed that increasing OP led to higher flux during ultrafiltration with limiting pressure (Plim). The limiting pressure (Plim) was anticipated to be beyond 3.0 bar due to the enzymatic pretreatment. The primary fouling mechanism during the clarification process was total pore blocking. After filtration, the resulting juice showed a significant reduction in turbidity of over 97, while TSS was lowered by 7–17 compared to fresh juice. The pomelo juice was efficiently clarified while the pH remained stable at ∼3.8. The clarified juice showed a minor decline of 10.1–13.9 in TPC and a 10.8–16.7 reduction in AAC compared to the fresh unclarified juice. In conclusion, a pressure of 3.0 bar is recommended for conducting the ultrafiltration process in order to attain desirable flux behavior and optimum properties of the juice.